The international school nurse asthma project: barriers related to asthma management in schools. (17th August 2012) - Svavarsdottir, Erla Kolbrun; Garwick, Ann W.; Anderson, Lori S.; Looman, Wendy S.; Seppelt, Ann; Orlygsdottir, Brynja
Abstract Aim This article is a report of an international study of barriers to asthma care from the perspectives of school nurses in Reykjavik, Iceland and St. Paul, Minnesota, in the context of their schools, communities and countries. Background Globally, asthma affects the health and school performance of many adolescents. School nurses play a key role by providing care to adolescents with asthma in school settings. Understanding universal barriers to asthma management in schools is important for developing interventions that are effective in multiple societal contexts. Design Exploratory, descriptive study. Methods Parallel studies were conducted from September 2008–January 2009, through six focus groups among school nurses (n = 32, in Reykjavik n = 17 and St. Paul n = 15) who were managing asthma in adolescents. Focus groups were audio‐recorded and transcribed verbatim in English or Icelandic. The Icelandic transcripts were translated into English. Descriptive content analytic techniques were used to systematically identify and categorize types of barriers to asthma care. Results School nurses in both countries identified common barriers, such as time constraints, communication challenges and school staff barriers. The primary difference was that St. Paul school nurses identified more socio‐economic and health access barriers than school nurses in Reykjavik. Conclusion Greater cultural and linguistic diversity and socio‐economic differences in the student population in St. Paul and lack of universal healthcare coverage in the US contributed to school nurses' need to focus more on asthma management than school nurses in Reykjavik, who were able to focus more on asthma prevention and education.